2018
DOI: 10.5194/se-2018-19
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Failure criteria for porous dome rocks and lavas: a study of Mt. Unzen, Japan

Abstract: Abstract. The strength and deformation mode (brittle vs ductile) of rocks is generally related to the porosity and pressure conditions, with occasional considerations of strain rate. At high temperature, molten rocks abide to Maxwell’s viscoelasticity and their deformation mode (brittle vs ductile) is generally defined by strain rate or reciprocally, by comparing the relaxation timescale of the material (for a given condition) to the observation timescale – a dimensionless ratio known as the Deborah (De) numbe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 13 publications
5
22
0
Order By: Relevance
“…This distinction is important because fresh, primary volcanic phenocrysts and groundmass are often microcracked (e.g., Heap, Lavallée, et al, ) as a result of their cooling histories (e.g., David et al, ; Vinciguerra et al, ). Hydrothermal alteration infills and/or seals these microfractures (e.g., Pola et al, , ; Wyering et al, , and references therein), which can strengthen a rock mass (e.g., Pola et al, , ; Wyering et al, , and references therein; Coats et al, ). In addition, hydrothermal alteration will change the mineral assemblage, changing the types of reactions possible during heating and cooling.…”
Section: Discussionmentioning
confidence: 99%
“…This distinction is important because fresh, primary volcanic phenocrysts and groundmass are often microcracked (e.g., Heap, Lavallée, et al, ) as a result of their cooling histories (e.g., David et al, ; Vinciguerra et al, ). Hydrothermal alteration infills and/or seals these microfractures (e.g., Pola et al, , ; Wyering et al, , and references therein), which can strengthen a rock mass (e.g., Pola et al, , ; Wyering et al, , and references therein; Coats et al, ). In addition, hydrothermal alteration will change the mineral assemblage, changing the types of reactions possible during heating and cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term petrology across the eruption was explored by Christopher et al (2014) and although they found systematic changes in Fe-content across time, they concluded that there was no progressive change of bulk composition, with SiO 2 content consistently between 56 and 62% throughout the eruption. However, previous studies have documented that geomechanical rock properties of chemically indistinguishable lavas can vary broadly as a result of distinct pore structures (Kendrick et al, 2013;Schaefer et al, 2015;Heap et al, 2016a), local heterogeneities (Farquharson et al, 2016), anisotropy (Bubeck et al, 2017), and post-emplacement alteration (Pola et al, 2014;Siratovich et al, 2014;Coats et al, 2018). We therefore aim to explore how the petrographic textures of the Soufrière Hills products and the temporal variation in these textures affect both rock strength and volcanic behavior, even where there is a narrow range in bulk rock compositions.…”
Section: Geological Settingmentioning
confidence: 99%
“…This is an important consideration when modeling structural dome instability, as using a constant UCS/UTS ratio in numerical models could result in overestimation of a dome's tensile strength, and therefore underestimation of the failure likelihood of the unconfined portion of lava domes. The current SHV dome at Montserrat is likely to have cooled to an extent where viscous flow no longer dominates eruptive behavior (Ball et al, 2015); as such, tests of rock properties at ambient temperatures are relevant to the modeling of ongoing stability of the volcano, but moreover, a number of studies have demonstrated that the strength of volcanic rock at elevated temperature is either comparable (Heap et al, 2014a(Heap et al, , 2018a or higher (Schaefer et al, 2015;Coats et al, 2018) than at room temperature, suggesting that domes are at their weakest following cooling.…”
Section: Co-variance Of Physical and Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations